Variational and asymptotic analysis of a static electro-elastic problem with Coulomb's law. (April 2023) - Manaa, Soumia; Benseridi, Hamid; Dilmi, Mourad
Abstract: The electro-elastic problem in a three-dimensional thin domain Ω ɛ is considered. In modeling the contact the Coulomb free boundary friction condition is used. First, we show the variational formulation of the problem and give the existence and the uniqueness of the solution. Then, we study the asymptotic analysis when then the small parameter ɛ tends to zero. A limit problem, the uniqueness result of the limit displacement and electric potential are obtained.